1931 Mich. Pub. Acts 670 - (:unkn) unknown (My University, 1931)
The Michigan Penal Code, ch. 37, §233: Any person who shall intentionally, without malice, point or aim any fire-arm at or toward any other person, shall be guilty of a misdemeanor.
Keywords: BRANDISHING